ISLAMISASI BUDAYA DALAM TRADISI TUJUH BULANAN (MITONI) DENGAN PEMBACAAN SURAT YŪSUF DAN MARYAM PADA JAMAAH SIMA’AN AL-QUR`AN DI DESA JURUG KECAMATAN MOJOSONGO KABUPATEN BOYOLALI - Laili Choirul Ummah (AL ITQAN: Jurnal Studi Al-Qur'an, 2018)
Acculturation is a social process arising from a particular culture which is confronted with other cultural elements, so that these elements can be accepted without losing their own cultural character. This study focuses on the interaction of the Qurʻan with Javanese culture, especially on the procession of traditions that undergoes Islamization, where Al-Qurʻan is involved in it. This occurs during the recitation of Surah of Yūsuf and Maryam in the seventh-month tradition (mitoni) in Jurug village, Mojosongo District, Boyolali Regency. The research problems discussed in this study are the causes which arises the factors of the emergence of a new culture, the factors that indicate the recitation of the Surah of Yūsuf and Maryam of Jurug village people. This study uses a qualitative research method. Data collection of this study uses participatory observation, including; interviews, observation, and documentation. With this acculturation concept, the researcher sees how the Qur'an began to infiltrate the daily lives of Jurug village people, and then uses it in the implementation of mitoni tradition by reciting the Surah of Yūsuf and Maryam in the procession of it. From the available data, as well as from the concept of acculturation, the researcher comes to a conclusion that the recitation of surah of Yūsuf and Maryam in Jurug village disseminates and grows as a norm that is believed to bring goodness and blessings to the mother and the baby she is carrying.